Analgesic Efficacy of Transversus Abdominis Plane block vs Local Infiltration of Lignocaine and Bupivacaine in Post-operative Patients - Shabbir Ahmad; Muhammad Kareemullah; Saeed Mahmood; Muhammad Azhar Alam; Qasim Farooq; Muhammad Rashid (Journal of University College of Medicine and Dentistry)
Objective: To compare the effectiveness of Transversus Abdominis Plane (TAP) block vs Local Infiltration for pain management techniques in patients undergoing laparoscopic lower abdominal surgeries. Methodology: This cross-sectional study was conducted at the Department of Surgery, Lahore General Hospital, from March to May, 2024. It involved a total of 110 patients, divided into two groups of 55 each, between the ages of 20 to 60 years, diagnosed with indirect inguinal hernia by ultrasound. Chronic smokers, drug addicts, intravenous drug abusers, patients with a history of previous surgeries, with known drug allergies and with complicated hernia were excluded from this cross-sectional study.  The Numerical Rating Scale (NRS) was used to see the pain variation and effectiveness of both techniques at 6, 12, 18 and 24 hours. Results: The mean age in the TAP Block Group was 32.0 ± 9.92 years, and the mean age in the Local Wound Infiltration Group was 34.21 ± 10.01 years. There were 108 (98.18%) male and 2(1.81%) female cases with a higher male-to-female ratio. The results indicated that the TAP Block group consistently required fewer rescue analgesic doses than the local wound Infiltration group at all postoperative time points. At 6 hours, 23.63% of patients in the TAP Block group needed additional analgesia, compared to 38.18% in the Wound Infiltration group, though this difference was not statistically significant. However, at 12, 18, and 24 hours, the TAP Block group showed a significantly lower need for rescue analgesia, with p-values of 0.002, and 0.008, respectively. Conclusion: In managing postoperative pain of Inguinal Hernia Repair, TAP Block is superior to Wound Infiltration of local anesthetic agent. After TAP Block NRS remains fewer and a smaller number of rescue doses are needed as compared to Wound infiltration.